Livestock Fish Mega Program to focus on specific value chains, working with development partners - Randolph, Thomas F. (International Livestock Research Institute, 2010)
Tom Randolph from ILRI introduces the essential features of the proposed CGIAR Livestock Fish Mega Program. The new elements for the CGIAR are basically the ways the Centers work with partners and how they focus their research. "Instead of doing our work everywhere, in bits and pieces, we are trying to focus it now into a few selected value chains in a few selected countries around the world, and we are going to commit to transforming those value chains and to work with development partners in large scale interventions as the research knowledge partner, in real time, helping them to have impact on a large number of smallholders, producing a greater amount of animal source foods for poor consumers." He was speaking in the margins of the CGIAR Livestock Fish Mega Program Livestock Fish Mega Program to focus on specific value chains, working with development partners